Interdisciplinary didactics alternative from the biological sciences with the professional practice disciplines in physical culture career of Pinar del Río - Idelfonso Javiqué-Leal; Isabel Pérez-Hernández; Arceny Rodríguez-Flores (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
When we applied alternatives and working algorism to put into practice the knowledge in the different subjects during the instructive- learning process it is important the exclusion of all empirical level in the teaching contents. The Biological science in essence constitutes a subject in the specific basic formation aimed to the integration of the future professional in the physical Culture majoring which has an important influence on the rest of the subjects that are part of the curriculum .In the present work we can show the results of one of the tasks corresponding to the research project related to the didactic changes in the Biological sciences subject, derived from the difficulties found in the teaching process. The authors give an approximation of how to deal with the different components in the teaching leaning- process with concrete results on the base theoretical and empiric methods. They give a work alternative to establish basic concepts with the didactic of the Physical education and sport showing advance evidences in the didactic order giving a high level of work in this subject.